Preconditioning optimization of hydraulic fracturing in block caving of hard rock mass - Min, Huang; Sijie, Cai; Mingqing, Huang; Xiaojun, Wang (Frontiers in Earth Science, 2023)
Introduction: Cavability issues often arise in hard rock mines employing the block caving mining method. Hydraulic fracturing stands out as a promising pre-conditioning technology for hard rock masses, with its pre-conditioning effects dependent on variable parameters. Methods: The impact of cluster number, injection rate, and liquid volume on fracture propagation was investigated through on-site hydraulic fracturing practices. Fracturability was initially verified via true triaxial fracturing tests, and preconditioning parameters were subsequently optimized using numerical simulations. The optimized on-site construction was monitored using electromagnetic methods. Results: The study revealed a negative correlation between fracture radius and the number of clusters, gradually decreasing with an increase in cluster number. However, the fracture weakening area increased with the rise in the number of clusters. The fracture weakening area also increased with the injection rate. Additionally, the fracture radius initially increased and then decreased. Both fracture weakening area and radius increased with an increase in liquid volume. The optimized parameters were identified as four clusters, an injection rate of 4 m3/min, and a liquid volume of 500 m3. Discussion: Building upon these findings, on-site experiments were conducted and monitored using electromagnetic methods. The monitored results demonstrated that the optimized parameters effectively achieved hydraulic fracturing expansion, accomplishing the goal of weakening hard rock.